2006
DOI: 10.1177/0040517506062454
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Stabilization under Various Conditions and Subsequent Treatment of Polyester Fabric on the Quantity and Composition of Extracted Oligomers

Abstract: The preparation of polyester fibers (PES) is usually carried out by polycondensation of dimethyl ester of terephthalic acids and diols using ester interchange. In addition to the polymer, both linear and cyclic oligomers are formed. The production of cyclic oligomers during the formation of poly(ethylene terephthalate) by melt polycondensation is inherent and therefore oligomers are natural constituents of all melt-extruded samples of the polymer [1]. Kricheldorf has proved that all step-growth polymerizations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Figure shows that a heavy mass of oligomers adhere on the dyed fiber surface with conventional dyeing method, but only a little remained when the PET fiber was dyed with the one-step method in an alkali bath. It is reported that the water solubility of the oligomers was less than 2 mg/L at 130 °C in acid condition . However, the ester bonds of oligomers (Figure ) can be hydrolyzed into carboxylate groups in alkali condition and the products can be easily dissolved in water …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure shows that a heavy mass of oligomers adhere on the dyed fiber surface with conventional dyeing method, but only a little remained when the PET fiber was dyed with the one-step method in an alkali bath. It is reported that the water solubility of the oligomers was less than 2 mg/L at 130 °C in acid condition . However, the ester bonds of oligomers (Figure ) can be hydrolyzed into carboxylate groups in alkali condition and the products can be easily dissolved in water …”
Section: Resultsmentioning
confidence: 99%
“…It is reported that the water solubility of the oligomers was less than 2 mg/L at 130 °C in acid condition. 40 However, the ester bonds of oligomers (Figure 8) can be hydrolyzed into carboxylate groups in alkali condition and the products can be easily dissolved in water. 41 Figure 6c−f shows that D4 and D5 have a similar build-up property and reflectance between conventional and one-step dyeing method.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Both of them were obtained from DSC results which are revealed in Table II. Degree of crystallinity is obtained as equation (1) express and some authors suggest (Hirao et al , 2010; Weon, 2010; Badía et al , 2009): Equation 1 Where ΔH c represents the crystallization enthalpy and ΔH 100 is the heat of crystallization for a 100 per cent crystalline PET, ΔH 100 =140 J/g (from literature) (Badía et al , 2009; Recelj et al , 2006).…”
Section: Resultsmentioning
confidence: 99%
“…The higher irradiation doses the higher degree of crystallization, although there are not significant changes on melting temperature. Some works shown that PET can change crystallinity and not vary melting temperature unless it is reprocessed (Recelj et al , 2006). We think that electron beam treatment induces oligomers to go through fibre surface and allows increasing crystallization.…”
Section: Resultsmentioning
confidence: 99%
“…As far as heat setting is concerned, polyester fibres are among the most studied fibres (Merian, Carbonell, Lerch, & Sanahuja, 1963;Radhakrishnan, Kanitkar, & Gupta, 1997;Recelj, Gorensek, & Zigon, 2006;Sardag, Ozdemir, & Kara, 2007); however, few investigations about heat setting of polyamide 6.6 fibres have been carried out. Venkatesh, Bose, Shah, and Dweltz (1978) heat set polyamide 6, polyamide 6.6 and polyester (polyethylene terephthalate) filament yarns at different temperatures in oil under a variety of experimental conditions.…”
Section: Introductionmentioning
confidence: 99%